Pengaruh Pendidikan Kesehatan Menggunakan Booklet Berbahasa Madura Terhadap Self Management Pada Klien Hipertensi di Poli Jantung Rsud dr. Abdoer Rahem Situbondo - Silvia Nuruddani; Handono Fatkhur Rahman; Setiyo Adi Nugroho; Sri Astutik Andayani; Abdul Hamid Wahid (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2019)
Objective: Hypertension is one of the main problems of public health, and if still a big challenge in indonesia with a high prevelention amounting to 34,1% (percent). Uncontrolled hypertension will cause complication and death. One of the factors that can cause hypertension is a bad self management. To improve self management on hypertensive dilent is health education needs to be done.Methods: The kind of quantitative research with Quasi Experiment design in the form of a Pretest-Posttest Nonequivalent Control Group sampale selection with Simple Random Samping as many as 40 respondets 20 intervention groups, 20 control graups data collection techniaques with self management questioner (H-SCALE).Results: Paired T-test results of the intervention group obtained a P-value of 0,000, and in the control group a P-value of 0.106 was obtained. While the results of the Independent T-test in the intervention group and the control group obtained a value of 0,000. So it can be said that there are effects and differences before and after health education is given to hypertension client self management. Conclusion: Expected by health education obout hypertension can improve self management on hypertension drent.